Checklist of the species of the Order Characiformes (Teleostei: Ostariophysi) - Toledo-Piza, Monica (2024)
A checklist of recent and fossil fishes of the Order Characiformes is presented herein and believed to be complete through 2022. A total of 47 collaborators checked and provided information about their taxa of expertise. The list is arranged in alphabetical order by family and then genus and includes all available synonyms. From a total of 3,087 species group names and 527 genus group names, 2,334 species are currently treated as valid, and assigned to 301 genera and 24 families. This total includes 25 species known only from the fossil record, of which 21 are assigned to eight extant families and four are Incertae sedis in Characiformes, but does not include five species based on fossil which were wrongly treated in Characiformes. The status of 79 nominal species remains unresolved. When there are two competing hypotheses about the validity of a name, one of them is chosen and the alternate interpretation is provided in the remark section of that name. Distributional summaries are presented as numbers that correspond to areas for which there is a record of occurrence of the species. A list of unavailable names is provided at the end since some of those names may need additional research to certify their status.